Barriers and enablers in primary care clinicians' management of osteoarthritis: protocol for a systematic review and qualitative evidence synthesis. Issue 5 (27th May 2016) - Egerton, T; Diamond, L; Buchbinder, R; Bennell, K; Slade, S C
Abstract : Introduction: Osteoarthritis is a highly prevalent and disabling condition. Primary care management of osteoarthritis is generally suboptimal despite evidence for several modestly effective interventions and the availability of high-quality clinical practice guidelines. This report describes a planned study to synthesise the views of primary care clinicians on the barriers and enablers to following recommended management of osteoarthritis, with the aim of providing new interpretations that may facilitate the uptake of recommended treatments, and in turn improve patient care. Methods and analysis: A systematic review and meta-synthesis of qualitative studies. 5 databases will be searched using key search terms for qualitative research, evidence-based practice, clinical practice guidelines, osteoarthritis, beliefs, perceptions, barriers, enablers and adherence. A priori inclusion/exclusion criteria include availability of data from primary care clinicians, reports on views regarding management of osteoarthritis, and studies using qualitative methods for both data collection and analysis. At least 2 independent reviewers will identify eligible reports, conduct a critical appraisal of study conduct, extract data and synthesise reported findings and interpretations. Synthesis will follow thematic analysis within a grounded theory framework of inductive coding and iterative theme identification. The reviewers plus co-authors will contribute to the meta-synthesis to find new themes and theories. The Confidence in the Evidence from Reviews of Qualitative research (CERQual) approach will be used to determine a confidence profile of each finding from the meta-synthesis. The protocol has been registered on PROSPERO and is reported using the Preferred Reporting Items for Systematic Review and Meta-Analyses Protocols (PRISMA-P) guidelines. Ethics and dissemination: Ethical approval is not required. The systematic review will be published in a peer-reviewed journal. The results will help to inform policy and practice and assist in the optimisation of management for people with osteoarthritis. PROSPERO registration number: CRD42015027543.